Methanolic Extract of Clinacanthus nutans Exerts Antinociceptive Activity via the Opioid/Nitric Oxide-Mediated, but cGMP-Independent, Pathways. (13th April 2016) - Abdul Rahim, Mohammad Hafiz; Zakaria, Zainul Amiruddin; Mohd Sani, Mohd Hijaz; Omar, Maizatul Hasyima; Yakob, Yusnita; Cheema, Manraj Singh; Ching, Siew Mooi; Ahmad, Zuraini; Abdul Kadir, Arifah
Abstract : The objectives of the present study were to determine the mechanisms of antinociceptive effect of methanol extract of Clinacanthus nutans (Acanthaceae) leaves (MECN) using various animal nociceptive models. The antinociceptive activity of orally administered 10% DMSO, 100 mg/kg acetylsalicylic acid (ASA), 5 mg/kg morphine, or MECN (100, 250, and 500 mg/kg) was determined using the acetic acid-induced abdominal constriction (ACT), formalin-induced paw licking (FT), and hot plate tests (HPT). The role of opioid and nitric oxide/cyclic guanosine monophosphate (NO/cGMP) systems was also investigated. The results showed that MECN produced a significant (p < 0.05 ) antinociceptive response in all nociceptive models with the recordedE D 50 value of 279.3 mg/kg for the ACT, while, for the early and late phases of the FT, the value was >500 mg/kg or 227.7 mg/kg, respectively. This antinociceptive activity was fully antagonized by naloxone (a nonselective opioid antagonist) but was partially reversed byl -arginine (l -arg; a nitric oxide [NO] precursor), N ω -nitro-l -arginine methyl ester hydrochloride (l -NAME; an NO synthase inhibitor), or their combinations thereof. In contrast, 1H-[1, 2, 4]oxadiazole[4, 3-a]quinoxalin-1-one (ODQ; a soluble guanylyl cyclase inhibitor) enhanced the extract's antinociception. UHPLC analysis revealed the presence of several flavonoid-based compounds with antinociceptive action. In conclusion, MECN exerted the peripherally and centrally mediated antinociceptive activity via the modulation of the opioid/NO-mediated, but cGMP-independent, systems.